Core/shell structural ultra-small gold and amyloid peptide nanocomposites with effective bacterial surface adherence and enhanced antibacterial photothermal ablation - Hanmeng Gui; Yonghai Feng; Li Qiang; Tongtong Sun; Lei Liu (Smart Materials in Medicine, 2021)
The exploration of ultra-small gold nanoparticles (Au NPs) (<5 ​nm) based photothermal nanoagent is important for antibacterial photothermal therapy due to their high biosafety. However, the ultra-small Au NPs usually have low absorption in near infrared (NIR) region, presenting poor NIR-based photothermal conversion. In the present work, a novel core/shell structural gold and amyloid peptide Aβ25-35 nanocomposites (Au@Aβ NCs) were constructed with ultra-small Au NPs (ca. 4.0 ​nm) as the core and Aβ25-35 oligomer as the shell (ca. 3 ​nm thickness) through the facile peptide templated chemical reduction method. The Au@Aβ NCs display enhanced NIR absorption and photothermal conversion efficiency as compared to pure Au NPs due to the extinction of Aβ shell. In addition, the Au@Aβ NCs can strongly adhere to the bacterial surfaces and aggregate together by virtue of the intrinsic self-assembly property of amyloid peptide, which facilitates the local photothermal ablation of bacteria. Consequently, the Au@Aβ NCs can fast and completely kill the pathogenic bacteria under NIR laser irradiation. This work provides an alternative strategy to prepare highly efficient ultra-small Au NPs based photothermal nanoagent for enhancing the antibacterial photothermal ablation.